Awareness and Perception of Sealer Puff among Libyan Dental Practitioners: A Cross-Sectional Survey - Ben Hakoma, Mohamed; Mohamed Jedeh (AlQalam Journal of Medical and Applied Sciences, 2024)
Sealer puff, the extrusion of endodontic sealers beyond the apex during root canal treatment (RCT), remains a topic of debate among dental professionals. Some consider it a sign of optimal obturation, while others associate it with complications such as inflammation. Limited data exist regarding dental practitioners' awareness and perception of sealer puff in countries with emerging healthcare systems, such as Libya. This study aimed to assess the awareness, perceptions, and practices of Libyan dental practitioners regarding sealer puff in endodontic treatment. A cross-sectional online survey was conducted over one month using Google Forms. The survey targeted dental practitioners in Libya who actively perform root canal treatments. The questionnaire covered demographics, RCT practices, knowledge of sealer puff, and perceptions of its clinical significance. Chi-square tests were used to analyze the associations between occupational status, years of experience, and perceptions of sealer puff. 160 dental practitioners participated. The majority were general practitioners (68.1%), with 60.6% having 1-3 years of experience. Most respondents performed fewer than three RCTs per week (50.6%), and 81.9% owned an apex locator. Perception of sealer puff varied, with 56.9% considering it a non-significant event and 34.4% viewing it as a sign of good obturation. Chi-square analysis revealed a significant association between occupational status and perception of sealer puff, (p < 0.001). The findings highlight the need for improved education on sealer puff among Libyan dental practitioners. Targeted programs should focus on enhancing practical skills and standardizing clinical guidelines to optimize endodontic outcomes. يعتبر "النفث السدادي"، وهو خروج مواد سد قنوات الجذور خارج القمة أثناء علاج قناة الجذر، موضوعًا جدليًا بين أطباء الأسنان. يعتبره البعض علامة على الإغلاق الجيد، بينما يربطه آخرون بمضاعفات مثل الالتهابات. توجد بيانات محدودة حول وعي وإدراك أطباء الأسنان بشأن النفث السدادي في البلدان ذات النظم الصحية الناشئة، مثل ليبيا. هدفت هذه الدراسة إلى تقييم الوعي والمفاهيم والممارسات بين أطباء الأسنان الليبيين بشأن النفث السدادي في علاج قنوات الجذور. تم إجراء استبيان مقطعي عبر الإنترنت لمدة شهر باستخدام نماذج قوقل. استهدف الاستبيان أطباء الأسنان في ليبيا الذين يقومون بعلاجات قنوات الجذور بشكل نشط. شمل الاستبيان بيانات ديموغرافية، وممارسات علاج قناة الجذر، ومدى العرفة بالنفث السدادي، ومفاهيم حول أهميته السريرية. تم استخدام اختبارات كاي-سكوير لتحليل العلاقات بين الوضع المهني وسنوات الخبرة والمفاهيم حول النفث السدادي. شارك ما مجموعه 160 من أطباء الأسنان. كانت الأغلبية من الممارسين العامين (68.1%)، وكان 60.6% منهم يمتلكون خبرة من 1 إلى 3 سنوات. أجرى معظم المشاركين أقل من ثلاثة علاجات قنوات جذر في الأسبوع (50.6%)، وامتلك 81.9% منهم جهاز محدد قمة الجذر. تنوعت المفاهيم حول النفث السدادي، حيث اعتبره 56.9% حدثًا غير مهم، بينما رآه 34.4% علامة على الإغلاق الجيد. كشف تحليل كاي-سكوير عن ارتباط كبير بين الوضع المهني والمفاهيم حول النفث السدادي (p < 0.001).تسلط النتائج الضوء على الحاجة إلى تحسين التعليم حول النفث السدادي بين أطباء الأسنان الليبيين. يجب أن تركز البرامج المستهدفة على تعزيز المهارات العملية وتوحيد الإرشادات السريرية لتحسين نتائج علاج قنوات الجذور